Is Blood Transfusion in Anesthesia Based on International Standard? - Parisa Akbarpour; Parisa Moradimajd; Azam Saei; jamile Abolghasemi (Archives of Anesthesia and Critical Care)
Background: Blood transfusion is a critical procedure where any error in the transmission chain can jeopardize patient safety. To ensure safe blood transfusions, it is essential to evaluate the performance of all personnel involved in the transfusion process, including anesthesia technologists, whose role has often been overlooked. This study was conducted with the aim of investigating the performance of in com anesthesia technologist plying with safe blood transfusion procedures during anesthesia. Methods: This cross-sectional study was conducted on 80 Anesthesia technologist s working in Rasoul Akram and Firouzgar hospitals in Tehran. The purpose of this study was to investigate the level of adherence to safe blood transfusion standards by Anesthesia technologist s. The data was collected using a comprehensive and standard questionnaire including two parts: the first part demographic information and the second part focusing on the standards of safe blood transfusion. All completed questionnaires were entered into SPSS software version 27. Descriptive and inferential statistics were used for statistical analysis. Results: The average age of the participants was 34 ± 10 years. Of the participants, 70% were women and 30% were men. The average score on the 36-question questionnaire was 27.32, corresponding to 73% of the maximum possible score. Performance levels were categorized as follows: good (75–100%), representing 41.25% of participants; moderate (50–75%), representing 58.75% of participants; and poor (<50%), with no participants falling into this category. Overall, the performance of anesthesia technologist in adhering to safe blood transfusion standards was considered average. Conclusion: Anesthesia technologist performance in safe blood transfusion procedures during anesthesia was evaluated at a moderate level. Addressing these gaps and considering educational programs in health care systems can improve patient safety and improve clinical outcomes during anesthesia and surgical procedures.